Labour Rights Index - WageIndicator Foundation (Netherlands); Centre for Labour Research (Pakistan) (2022)
The Labour Rights Index is a comparative tool, an international qualification standard, which allows its users to compare labour legislation around the world. In a way, it helps you navigate the labour markets of 145 countries. The labour market regulation affecting around more than 90% of the 3.5 billion global labour force has been analysed and scored under the Index. The aim is to make all this abstract legal information accessible to workers in order to improve their working lives. Similarly, the work is useful for national and trans-national employers to ensure compliance with local labour legislation. --Website description